Business Consulting para la empresa TOPSERMIN - Britto Hernandez, Carla Teresa (2025)
For almost a decade, TOPSERMIN E.I.R.L. has operated across the country, offering mining and construction services. It is a specialized company. The organization provides services to private sectors, but because the latter requires a greater degree of flexibility in project management, it focuses mostly on the former. Its main services are underground and surface topographic surveying, management of topographic software, diamond drilling for geotechnical, hydrogeological and exploration purposes, geomechanical evaluations, and construction supervision and quality control. Among its main clients are Southern Copper, SIMSA, Nexa Resources, Company Minera Chuvilca S.A., MILPO, Grupo Unión S.A.C., Antamina, Company Minera Condestable S.A., and Mining Explorations San Ramón. To identify the main problem, interviews were carried out with the general manager, the contract administrator and the project manager, concluding that the reduction of the project portfolio is the main concern. It was found that the three primary factors that produce it are: an increase in the variety of projects are the provision of different services to the private sector; a fortification of rivals commercial and marketing administrations; and an increased amount of capital available for investments. Additionally, a theoretical foundation for the formulation of five improvement options – the development of strategic management methods, marketing strategies, cost management software (ERP), balanced scorecard, and process standardization – was established through the preparation of external and internal review as well as an analysis of concepts and definitions. In keeping with this, each improvement option was given a thorough execution plan that included financial allotments, including deadlines, responsibilities and budget allocations with an initial date from October to December 2023, tangible costs amount to S/ 8,700 and intangible costs amount to S/ 55,575, making a total initial investment of S/ 64,275. The total investment cost, both tangible and intangible, amounts to S/ 400,175 for the 15 months that the project lasts. In terms of the quantitative benefits, an economic and financial analysis was conducted that provided proof of the proposal`s viability under optimistic circumstances. The results included a third-year recovery period (PAYBACK), an Internal Rate of Return (IRR) of 92,29%, and a Net Present Value (NPV) of S/ 722,037.88. The results were similarly positive under negative circumstances, with a fifth-year PAYBACK, an IRR of 33.47%, and an NPV of S/ 115,374.02.